Haptoglobin, alpha-thalassaemia and glucose-6-phosphate dehydrogenase polymorphisms and risk of abnormal transcranial Doppler among patients with sickle cell anaemia in Tanzania - Cox, S.E.; Makani, J.; Soka, D.; L'Esperance, V.S.; Kija, E.; Domínguez Salas, Paula; Newton, C.R.J.; Birch, A.A.; Prentice, A.M.; Kirkham, F.J. (Wiley, 2014)
Transcranial Doppler ultrasonography measures cerebral blood flow velocity (CBFv) of basal intracranial vessels and is used clinically to detect stroke risk in children with sickle cell anaemia (SCA). Co-inheritance in SCA of alpha-thalassaemia and glucose-6-phosphate dehydrogenase (G6PD) polymorphisms is reported to associate with high CBFv and/or risk of stroke. The effect of a common functional polymorphism of haptoglobin (HP) is unknown. We investigated the effect of co-inheritance of these polymorphisms on CBFv in 601 stroke-free Tanzanian SCA patients aged <24 years. Homozygosity for alpha-thalassaemia 3·7 deletion was significantly associated with reduced mean CBFv compared to wild-type (β-coefficient −16·1 cm/s, P = 0·002) adjusted for age and survey year. Inheritance of 1 or 2 alpha-thalassaemia deletions was associated with decreased risk of abnormally high CBFv, compared to published data from Kenyan healthy control children (Relative risk ratio [RRR] = 0·53 [95% confidence interval (CI):0·35–0·8] & RRR = 0·43 [95% CI:0·23–0·78]), and reduced risk of abnormally low CBFv for 1 deletion only (RRR = 0·38 [95% CI:0·17–0·83]). No effects were observed for G6PD or HP polymorphisms. This is the first report of the effects of co-inheritance of common polymorphisms, including the HP polymorphism, on CBFv in SCA patients resident in Africa and confirms the importance of alpha-thalassaemia in reducing risk of abnormal CBFv.